2000
DOI: 10.1002/(sici)1521-4109(20000401)12:6<429::aid-elan429>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior and Determination of Ketoconazole from Pharmaceutical Preparations

Abstract: The oxidation of ketoconazole (KC) was investigated by rotating disk electrode voltammetry, cyclic voltammetry, and controlled potential coulometry in chloroform at platinum (Pt), gold (Au), and glassy carbon (GC) electrodes using tetrabutylammonium perchlorate as supporting electrolyte. Based on the electrochemical results obtained, the following possible mechanism was proposed to explain the electrochemical oxidation of KC KC Àe ÀÀÀB AÀÀÀ KC Á À À À? Àe P j ; P H A differential pulse voltammetric method at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…[9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: 8mentioning
confidence: 99%
“…7,8 We recently studied the electrochemical behavior and some chemical properties of various antifungal drugs containing piperazine or imidazole groups such as, ketoconazole in aqueous and non-aqueous media. [9][10][11][12] In this work, we initially studied the reaction between clotrimazole (CT) (a drug containing an imidazole ring) and triiodide ions. We found that the protonated clotrimazole (CTH + ) is precipitated in the presence of excess I3 -ions as a (CTH)I3 ion pair.…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism of action of KC and azoles, in general, is the inhibition of sterol 14-a-dimethylase, a microsomal cytochrome P-450 dependent enzyme system. 5 Thus, due to the vital importance of determination of this drug in pharmaceutical preparations and biological fluids, several spectroscopic, [6][7][8][9][10][11][12][13] high performance liquid chromatographic, 14-18 electrochemical [19][20][21][22][23] and titrimetric 24 methods for the assay of KC have been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently studied the electrooxidation of KC in aqueous and non-aqueous media. [20][21][22] Based on the electrochemical results obtained, in the following step, we investigated the chemical oxidation of KC in solution and developed a new spectrophotometric method for the determination of KC based on the oxidation with Iron(III) in acidic citrate buffer solutions. 25 The present work represents the first attempt in the kinetic study of the reaction between KC and potassium permanganate in alkaline solutions in order to de-velop a kinetic-spectrophotometric method for the determination of KC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shamsipur et al [16] developed a triiodide PVC membrane sensor based on a charge-transfer complex of I 2 with 2,4,6,8-tetraazabicyclo [3.3.0] octane and used it as an indicator electrode in potentiometric titration of triiodide ions. We have recently studied the electrochemical behavior and some chemical reactions of ketoconazole (KC) (an antifungal drug) in aqueous and non-aqueous media [17,18]. Also, we have found that the protonated KC (as dication) is precipitated in the presence of I À 3 ions as (KCH 2 )(I 3 ) 2 ion pair.…”
Section: Introductionmentioning
confidence: 99%